The manipulation of top-down interpretation as one’s symptomatic body reduces the sense of body ownership - Yamamoto, Kazuki; Nakao, Takashi (Frontiers in Psychology, 2024)
Sense of body ownership has been studied using rubber hand illusion (RHI) and full-body illusion (FBI). It has recently become clear that consciously interpreting a fake body as one’s own in a top-down manner influences these body illusions. Furthermore, a study interestingly found that the influence of top-down interpretation was moderated by the degree of depersonalization, which was a symptom of a lack of sense of body ownership. In a case study on depersonalization, the top-down interpretation of one’s body was suggested to be a negative physical state that made it difficult to feel a sense of body ownership. However, this has not been examined. We examined the influence of negative top-down interpretation using an FBI procedure. A fake body was instructed to be viewed as a negative self-body (“view the virtual body’s back while regarding the virtual body as your own experiencing abdominal pain”). To examine the influence of a negative top-down interpretation, participants were instructed to interpret the body as their own (neutral self-body) as a control condition. We used skin conductance responses to a fearful stimulus presented after an illusion procedure to measure the degree of FBI experienced. Results indicated a significant difference in the skin conductance response between the synchronous and asynchronous presentation of visual-tactile stimuli in the control condition, which confirmed the occurrence of the illusion. However, the occurrence of the illusion was not confirmed when the participants were instructed to interpret the virtual body as their own in a negative physical state, and the degree of FBI was smaller than the control condition. Our finding that an FBI was inhibited by manipulation of the top-down interpretation suggested that it could be a factor that inhibited the creation of a sense of body ownership.